Arctic sea ice is an important temporal sink and means of transport for microplastic - Ilka Peeken; Sebastian Primpke; Birte Beyer; Julia Gütermann; Christian Katlein; Thomas Krumpen; Melanie Bergmann; Laura Hehemann; Gunnar Gerdts (Nature Communications, 2018)
Microplastic (MP) pollution in polar regions is a growing environmental concern, yet little is known regarding the role of sea-ice as a sink and transport vector of MPs. Here, the authors show that MPs in sea-ice have no uniform polymer composition and observe unique MP patterns in different sea-ice horizons.